2020
DOI: 10.22159/ajpcr.2020.v13i6.37196
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Fishball on Various Concentration of Carrageenan From Different Harvest Time of Kappaphycus Alvarezii

Abstract: Objective: This paper investigates the effect of carrageenan from various harvest times on fishball characteristics. The harvest time consists of three different periods (40 days, 45 days, and 50 days) from Bontang Coastal, East Kalimantan, Indonesia. Methods: The carrageenan fortified to fishball used two concentrations that were 0.25% and 0.5%.The proximate analysis, including moisture, ash, protein, fat, and carbohydrate, showed significantly different (p < 0.05). The texture analysis showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…with DW, 0.1% NaCl, and CaCl 2 solution (p < .05). However, there was comparatively lower protein content observed in mackerel fish ball (13.40%-15.23%) (Asikin et al, 2020) and Indian mackerel fish ball (12.94%) (Alkuraieef et al, 2020) than the current study. The fish species in this study contains higher protein in its raw state and that might result in higher protein in the mince-blend fish ball.…”
Section: Proximate Compositioncontrasting
confidence: 86%
See 3 more Smart Citations
“…with DW, 0.1% NaCl, and CaCl 2 solution (p < .05). However, there was comparatively lower protein content observed in mackerel fish ball (13.40%-15.23%) (Asikin et al, 2020) and Indian mackerel fish ball (12.94%) (Alkuraieef et al, 2020) than the current study. The fish species in this study contains higher protein in its raw state and that might result in higher protein in the mince-blend fish ball.…”
Section: Proximate Compositioncontrasting
confidence: 86%
“…Several studies report that fish ball is an important mince/surimibased value-added fish product (Affandi et al, 2019;Alkuraieef et al, 2020;Chowdhury et al, 2017;Ibrahim, 2015;Asikin et al, 2020;Zhao et al, 2019). Among the foods that are "ready to eat" or "ready to cook," fish ball is a popular and tasty value-added fish product (Dutta, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several researches also demonstrated that the chemical composition of seaweeds (such as sulphate content, molecular weight and 3,6‐anhydrogalactose) varies with ecological conditions (Asikin et al ., 2020; Yu et al ., 2021). The change of harvest geographical location and season can promote or inhibit the biosynthesis of chemical components in seaweeds, which leads to the variety of antioxidant activity of polysaccharides (Monteiro et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%